Digital campus - Basri, Siti Nur Ain; Ahmad, Faridahanim; Abidin, Nur Izie Adiana; Baba, Ishak; Harun, Hasnida; Abdul Hamid, Nor Hazren; Awang, Mariah; Abdul Rahman, Muhammad Ashraf; Musa, Muhammad Kamaruzaman; Hamidon, Nuramidah; Ahmad, Suhaida; Ahmad, Suhaila; et al. (Science Publishing Corporation, 2020)
Mobile is everywhere, changing the way we work, play, socialize, and learn. Students nowadays are immersed in a digital culture driven by mobile consumer experiences across a range of devices, from wearable to phones, tablets and virtual-reality platforms. Digital Campus is a website application that is in University Tun Hussien Onn Pagoh Campus. The purpose of this website is to search all locations located in Pagoh Campus such as laboratory, admin office, dean office, cafe and classroom. Digital campus website is embedded with Open Street Map. It is open databased licensing and it is a collaborative mapping. This website is developed using Joomla 3.8.13 with PHP version, 5.6.25. There are 204 locations were plotted using this link https://digitalcampus.uthm.edu.my/index.php. Digital campus based on Open Street Map can helps students, admin staff, lectures and visitors to find location in very easy way by using digital platform. Thus, this application facilities can optimization of administration work and promote university management to higher performances.